Cellular Autofluorescence following Ionizing Radiation - Schaue, Dörthe (Public Library of Science, 2012)
Cells often autofluoresce in response to UV radiation excitation and this can reflect critical aspects of cellular metabolism. Here we report that many different human and murine cell types respond to ionizing radiation with a striking rise in autofluorescence that is dependent on dose and time. There was a highly reproducible fluorescent shift at various wavelengths, which was mirrored by an equally reproducible rise in the vital intracellular metabolic co-factors FAD and NADH. It appears that mitochondria, metabolism and Ca(2+) homeostasis are important for this to occur as cells without mitochondria or cells unable to alter calcium levels did not behave in this way. We believe these radiation-induced changes are of biological importance and that autofluorescence may even provide us with a tool to monitor radiation responses in the clinic.